Analisis Pengaruh Tata Kelola Perusahaan dan Karakteristik Auditor terhadap Audit Fee melalui Jenis Industri sebagai Variabel Intervening - Maharani, Destin Alfianika (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2024)
Audit fees are defined as fees received by external auditors after completing tasks assigned by the company. The external auditor is entitled to receive remuneration in accordance with the agreed agreement and set forth in the engagement letter. An audit fee that is too low or too high can affect the level of independence of the auditor. Therefore, this research aims to determine the partial and simultaneous influence of corporate governance, auditor characteristics, type of industry on audit fees. In addition, this research also aims to find out whether there is a direct or indirect effect of corporate governance and auditor characteristics on audit fees through the type of industry. This research was conducted on companies registered in the Corporate Governance Perception Index (CPGI) for the period 2017 – 2019 by selecting the sample using purposive sampling. Partially the results of the research show 1) Corporate governance has a positive and significant effect on audit fees 2) Auditor characteristics and type of industry have a negative and insignificant effect on audit fees 3) Corporate governance has a positive and insignificant effect on industry types 4) Auditor characteristics have an effect positive and significant to the type of industry 5) Corporate governance and auditor characteristics have a greater direct effect than the indirect effect on audit fees through the type of industry. Meanwhile, this research shows that there is a simultaneous influence between corporate governance, auditor characteristics and type of industry simultaneously influencing audit fees.